A facile self-templating synthesis of carbon frameworks with tailored hierarchical porosity for enhanced energy storage performance. Issue 36 (21st April 2017) - Yang, Jie; Li, Gaoran; Cai, Meidan; Pan, Pengju; Li, Zhoupeng; Bao, Yongzhong; Chen, Zhongwei
Abstract : A well-tailored hierarchical porous carbon framework was developed from poly(vinylidene chloride)-based block copolymers with great superiority to meet the target-oriented structural demands in energy storage systems. Abstract : Herein, we present a facile synthesis of hierarchical carbon frameworks with microporous skeletons and interconnected meso/macropores by employing poly(vinylidene chloride- co -methyl acrylate)- b -polystyrene copolymers as precursors. The obtained porosity can be tuned over a broad range via well-selected block proportions of the precursor, enabling its advantageous applications in target-oriented energy storage systems.